Fundamentals of statistics: volume two - Goon, A.M.; Gupta, M.K.; Dasgupta, B. (Calcutta: The world press, 1968)
This two-volume work on statistical theory (as distinct from statistical methods) aims at acquainting the reader with the mainstream of present-day statistical thinking. Volume one starts with a brief description of measure theory and presents the theory of probability and that of probability distributions within a measure-theoretic framework. The subject of sampling distributions, that follows, is treated in great detail. Limit theorems receive considerably greater attention than they generally do in books of this kind.
Analysis of variance -- Designs of experiments -- Designs of sample surveys -- Vital statistical methods -- Statistical methods for psychology and education --Index number -- Analysis of time series -- Demand analysis -- Statistical quality control
Includes index and appendices.
Keywords: Statistics; Statistical mathematics; Statistical theory and methods; Fundamental statistics